Report of the Evaluation Study on the Scheme "Modernization of Office Systems" of Planning Commission Government of India - Planning Commission (Planning Commission, 2005)
The Scheme launched in 1987-88, aimed at ""making the planning process, namely plan formulation, implementation, follow-up and evaluation more efficient and effective through improvement in the Information Technology and provision of modern offices and equipment facilities"". The launch of a separate Scheme for modernizing or upgrading the systems and procedures in Planning Commission was done keeping in view the special role and responsibility of Planning Commission in the National Planning. However, as our study revealed, the advantages that could have accrued through such a Scheme, unfortunately did not come through fast enough. The fact that the Scheme is in operation for the last 18 years with a total expenditure of Rs. 22.15 crore (excluding the provision of Rs. 60 crore for the year 2004-05) clearly points to flaws in initial plan formulation and design of the Scheme. It was apparent that a detailed analysis of the requirements of IT hardware/software and other improvements needed were not worked out. The result was a very weak and poor implementation process
Planning Commission Government Of India Institute Of Public Auditors Of India New Delhi